Physical activity through the cancer trajectory - Walsh, Julie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2012)
With earlier diagnosis and newer targeted treatments for cancer, the numbers expected to survive this diagnosis continue to increase. Therefore, the longer term health and well-being of cancer survivors is garnering increased attention. Physical activity is of importance throughout the cancer trajectory.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin